Experimental study of shear strength and CBR improvement of silty clay soil reinforced with waste tires - Kamel Bezih; Mohamed Djenane; Mohamed Laouche; Kamel Hebbache (Scientific Reports)
Abstract This study explores the potential of using waste tires to reinforce silty clay soils for various geotechnical applications. Direct shear tests were conducted to evaluate the cohesion and internal friction angle of the reinforced soil, while California Bearing Ratio (CBR) tests were performed to determine its load-bearing capacity. For the direct shear tests, two types of waste tire aggregates (0/3 mm and 0/6 mm) were added to the soil at different weight percentages: 10%, 20%, 30%, and 40%. In the CBR tests, the percentages used were 2.5%, 5%, 7.5%, 10%, and 12.5%. These tests aimed to assess the soil’s mechanical behavior by analysing changes in cohesion, friction angle, and CBR values-three critical factors for stability and strength. To simulate different compaction intensities, the mixtures were compacted with 11, 25, and 55 blows per layer. The results indicate that adding 40% recycled tire granules significantly improved the soil’s shear resistance, leading to an increase in both cohesion and internal friction angle. Additionally, substantial improvements in CBR values suggest enhanced load-bearing capacity, particularly with higher compaction energies. The study found that a tire content of 7.5% is optimal for maximising CBR values, confirming the effectiveness of tire reinforcement at this level. This research highlights the practicality of using recycled tires for soil reinforcement, demonstrating that while higher reinforcement percentages can be beneficial, their efficiency diminishes beyond a certain threshold. Utilising waste tires in geotechnical engineering not only enhances soil performance but also contributes to sustainable waste management.